Implementation of TPACK in Microteaching of Mathematics Education Students Based on Online Learning Platforms - Juhaevah, Fahruh; Kaliky, Syafruddin (Universitas Muhammadiyah Mataram, 2023)
The purpose of this study was to determine the effectiveness of the implementation of TPACK in microteaching mathematics education students in terms of differences in online learning platforms. The type of research used in this study is Mixed Method with a Sequential Explanatory design by starting with quantitative data collection and then continuing with qualitative data collection.. The subjects in this study consisted of 12 mathematics students. Subjects were given a TPACK ability test and the opportunity to simulate learning using an online learning platform, then conducted in-depth interviews regarding the implementation results. The results showed that there were differences in the ability to implement student TPACK in microteaching consisting of PCK components including basic skills of explaining and asking, TPK components covering basic skills of explaining and providing reinforcement, TCK components covering basic skills of explaining and providing variations, and TPACK components covering basic skills of opening and closing as well as essential skills of managing small groups. Based on the two platforms used, Moodle is better when compared to Google Classroom in supporting and making it easier for students to implement TPACK when compared to using Google Classroom. Especially in terms of appearance, features, integration with other applications, and storage limits. It can be stated that Moodle is more effective when compared to Google Classroom in implementing TPACK in microteaching.